Body image and weight loss diet behavior are related to nutritional status in female college students - Zahra Zakiyah Komarudin; Prita Dhyani Swamilaksita; Khairizka Citra Palupi; Harna Harna; Dudung Angkasa (AcTion: Aceh Nutrition Journal, 2023)
Nutritional status is an important indicator of college student health. College students are included in the age group vulnerable to nutritional problems such as decreased diet quality and excessive weight. The study aims to determine the relationship between body image, mindful eating, and weight loss diet behavior with nutritional status in female college students. The study used a cross-sectional design and was conducted among female students at Esa Unggul University in 2022. A total of 122 subjects were selected using the Proportionate Stratified Random Sampling method. Nutritional status is measured by assessing Body Mass Index (BMI). The instruments used were the Multidimensional Body-Self Relations Questionnaire (MBSRQ) to assess body image, the Mindful Eating Questionnaire (MEQ) to assess mindful eating, and the dietary behavior questionnaire to assess weight loss. Data were analyzed by chi-square test at CI:95%. The results showed that body image was related to thin (p= 0,004) and obese (p= 0,000) nutritional status. Dietary behavior for weight loss is associated with thin nutritional status (p= 0,010) but not with obesity (p= 0,389). In conclusion, nutritional status (BMI) is related to body image and weight loss diet behavior in female college students.